2018
DOI: 10.1007/s11606-017-4281-x
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Medication and Dementia Risk in Older Adult African Americans with Hypertension: A Prospective Cohort Study

Abstract: BackgroundAfrican Americans are especially at risk of hypertension and dementia. Antihypertensive medications reduce the risk of cardiovascular events, but may also reduce the risk of dementia.ObjectiveTo assess the longitudinal effects of antihypertensive medications and blood pressure on the onset of incident dementia in a cohort of African Americans.DesignProspective cohort.Participants1236 community-dwelling patients from an inner-city public health care system, aged 65 years and older, with a history of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…18 Seven studies diagnosed AD using NINCDS-ADRDA criteria. 24,26,28,29,32,34,36 Seventeen studies analyzed all-cause dementia, [17][18][19][20][21][22][23][25][26][27][31][32][33][35][36][37][38] and 5 AD only. 24,28e30,34 Follow-up ranged from 2.2 22,32 to 11 28 years (median¼4.3).…”
Section: Resultsmentioning
confidence: 99%
“…18 Seven studies diagnosed AD using NINCDS-ADRDA criteria. 24,26,28,29,32,34,36 Seventeen studies analyzed all-cause dementia, [17][18][19][20][21][22][23][25][26][27][31][32][33][35][36][37][38] and 5 AD only. 24,28e30,34 Follow-up ranged from 2.2 22,32 to 11 28 years (median¼4.3).…”
Section: Resultsmentioning
confidence: 99%
“…This may reflect protective effects of DiCCB beyond angiotensin II stimulation (e.g., stimulating angiogenesis), 6 , 15 or chance/bias from the study's relatively small number of DiCCB users, high number of comparisons, and observational design. Previous studies have found both lower 7 , 9 , 41 and higher 42 , 43 dementia risks for calcium channel blockers (CCBs) compared to ARBs and also lower 42 44 and higher 7 , 9 , 41 , 45 dementia risks for CCBs compared to diuretics. However, none of these were significant in direct comparison.…”
Section: Discussionmentioning
confidence: 99%
“…In general, blood pressure can be easily controlled by various medications. Numerous studies have revealed no differences between individuals using anti-hypertensive medications and those without hypertension [ 89 , 93 ]. It has also been observed that the control of blood pressure during the lifetime, especially during sleep, can significantly decrease the risk for development of dementia in later life [ 84 ].…”
Section: Other Established (Non-)modifiable Risk Factors and Possimentioning
confidence: 99%
“…We remind the reader that, for instance, midlife obesity is often associated with hypertension and diabetes mellitus. These three possibly modifiable risk factors can cause an accumulation of neurotoxic peptides and oxidative stress level changes in the brain that in time may result in cognitive impairment and dementia [ 78 , 81 , 89 ]. Similarly, the higher risk of dementia in the elderly individuals with various comorbid cardiometabolic diseases such as diabetes mellitus or stroke can be moderated by social engagement and physical activities [ 131 ].…”
Section: Future Possible Research Directions and Trends In The Trementioning
confidence: 99%